Odpowiedzi

2009-11-15T19:36:08+01:00
2009-11-15T19:37:49+01:00
A)
6 7/9 - (4 7/18 - 1 5/6)= 6 7/9 - (3 25/18 - 1 15/18) = 6 7/9 - 2 10/18= 6 7/9 - 2 5/9 = 4 2/9

b) 6 1/3 - 2 3/4 + 3 5/6 = 6 4/12 - 2 9/12 + 3 10/12= 5 16/12 - 2 9/12 + 3 10/12 = 3 7/12 + 3 10/12= 6 17/12 = 7 5/12
Najlepsza Odpowiedź!
2009-11-15T19:37:45+01:00
A) 6 7/9 - (4 7/18 - 1 5/6)= 6 14/18 - (4 7/18 - 1 15/18)=6 14/18 - (3 25/18 - 1 15/18)=6 14/18 - 2 10/18 = 4 4/18
b)6 1/3 - 2 3/4 + 3 5/6= 6 4/12 - 2 9/12 + 3 10/12= 5 16/12 - 2 9/12 + 3 10/12= 3 7/12 + 3 10/12 = 6 17/12 = 6 5/12
;)
1 5 1